Plasma Phospholipid and Sphingolipid Alterations in Presenilin1 Mutation Carriers: A Pilot Study - Pratishtha Chatterjee; Wei Ling Florence Lim; Guanghou Shui; Veer Bala Gupta; Ian James; Anne M. Fagan; Chengjie Xiong; Hamid R. Sohrabi; Kevin Taddei; Belinda M. Brown; Tammie L.S. Benzinger; Colin L. Masters; et al. (2016)
Background and Objective:Aberrant lipid metabolism has been implicated in sporadic Alzheimer's disease (AD). The current study investigated plasma phospholipid and sphingolipid profiles in individuals carrying PSEN1 mutations responsible for autosomal dominant AD (ADAD). Methods:Study participants evaluated were from the Perth and Melbourne sites of the Dominantly Inherited Alzheimer Network (DIAN) study. Plasma phospholipid and sphingolipid profiles were measured using liquid chromatography coupled with mass spectrometry in 20 PSEN1 mutation carriers (MC; eight of whom were symptomatic and twelve asymptomatic, based on Clinical Dementia Rating scores) and compared with six non carriers (NC) using linear mixed models. Further, AD gold standard biomarker data obtained from the DIAN database were correlated with lipid species significantly altered between MC and NC, using Spearman's correlation coefficient. Results:One-hundred and thirty-nine plasma phospholipid and sphingolipid species were measured. Significantly altered species in MC compared to NC primarily belonged to choline and ethanolamine containing phospholipid classes and ceramides. Further phosphatidylcholine species (34:6, 36:5, 40:6) correlated with cerebrospinal fluid tau (p < 0.05), and plasmalogen ethanolamine species (34:2, 36:,4) correlated with both cerebrospinal fluid tau and brain amyloid load within the MC group (p < 0.05). Conclusion:These findings indicate altered phospholipid and sphingolipid metabolism in ADAD and provide insight into the pathomolecular changes occurring with ADAD pathogenesis. Further, findings reported in this study allow comparison of lipid alterations in ADAD with those reported previously in sporadic AD. The findings observed in the current pilot study warrant validation in the larger DIAN cohort.